COVID-19 Vaccine Inequities and Hesitancy in Iraq : Results from June, July, and August 2021 Rounds of Iraq High Frequency Phone Survey (IHFPS) - World Bank (Washington, DC, 2022)
While Iraq continues to experience a surge in the number of coronavirus cases, the proportion of the country’s population that is vaccinated remains very low. For a more in-depth understanding of the state of vaccination in Iraq, this note presents findings on Coronavirus (Covid-19) vaccination disparities and hesitancy from the last three rounds of the Iraq High Frequency Phone Survey (IHFPS) conducted between June and August 2021. Findings from the survey suggest a low but increasing vaccination trend among adult Iraqis, however, resistance to the vaccine remain high. Fear and mistrust towards the Covid-19 vaccine risks to undermine the efficacy of the country’s vaccination campaign. Low vaccination rate and the important disparities that have emerged in vaccination and vaccine hesitancy highlight the need for a robust and more inclusive vaccination campaign.